The Top-100 most cited articles on dural arteriovenous fistula: A bibliometric analysis - Alkhaibary, Ali (J Cerebrovasc Endovasc Neurosurg, 2021)
OBJECTIVE: Dural arteriovenous fistula (DAVF) is a rare pathological vascular lesion with variable clinical manifestations. Since 1968, several articles have been published to address spinal and cranial DAVFs. The aim of this study is to identify, analyse, and review the pertinent literature of the top-100 most cited articles on DAVFs published to date. METHODS: A title-specific, keyword-based search with no time restriction was performed in June 2020. The Scopus database was used to identify the top-100 most cited articles on DAVFs. The term “dural arteriovenous fistula” was used as a search keyword. The search results were arranged in descending order based on the total citation count. The top-100 articles were categorized into ten categories. RESULTS: Between 1968 and 2020, a total of 2298 articles were published on DAVFs. The top-100 most cited articles were published between 1983 and 2012. The total number of citations for the top-100 articles was 12393 (123 citations/article). Most articles (34%) were investigating the clinical aspect of DAVFs. The country contributing to the most impactful and highest volume of publications (46%) was the United States. The Mayo Clinic was the most active institute in contribution. Most articles (29%) were published by the Journal of Neurosurgery. CONCLUSIONS: In the top-100 most cited articles on DAVF, most studies were published in neurosurgery/neuroradiology-dedicated journals. This bibliometric analysis identifies the publication trends and provides a comprehensive overview of the most influential articles addressing DAVFs.